Effect of Temperature and Brewing Time on Characteristics Chemical and Sensory of Liang Tea Pontianak - Evy Fannia; Yohana Sutiknyawati Kusuma Dewi; Sulvi Purwayantie (Jurnal Teknologi Hasil Pertanian, 2024)
Liang tea Pontianak consists of herbal ingredients (Dicliptera chinensis leaves, Tradescantia spathacea leaves, Origanum vulgare Wilder leaves, Pandanus amarillifolius leaves and skin of Aloe vera chinensis) and tea ingredients (Caesalpinia sappan wood). Technological developments for preparing tea burrows in fresh form have turned into dry ingredients so that they are practical in preparation. The process of serving liang tea Pontianak by brewing, but currently it is not known when and the brewing temperature that produces the best physicochemical characteristics of the burrow has not been studied. The target of this research was to obtain the temperature and brewing time that produces the best chemical and sensory characteristics of Liang tea Pontianak. This study used a factorial randomized block design (RBD) consisting of 2 treatment, namely the brewing temperature of 70±3°C, 85±3°C and 100°C while the second factor was the length of brewing, consisting of 5, 10, 15 and 20 minutes. The results of this study found that the chemical and sensory characteristics of Liang tea Pontianak were brewed at 100°C for 20 minutes. The physicochemical characteristics of Liang teh Pontianak have antioxidant activity of 73.81%, total phenol content of 97.58 mg GAE/g and flavonoid content of 217.28 mg QE/g. Based on sensory characteristics, the best brewing Liang Teh Pontianak was 70±3°C for 20 minutes with color attribute values of 4.28, aroma 3.80, and taste 3.64. Determination of the best treatment using the value of the effectiveness index.